Down-regulation of inhibitor of apoptosis levels provides competence for steroid-triggered cell death. - Yin, V.P.; Thummel, C.S.; Bashirullah, A. (Journal of Cell Biology, 2007)
A pulse of the steroid hormone ecdysone triggers the destruction of larval salivary glands during Drosophila metamorphosis through a transcriptional cascade that converges on reaper (rpr) and head involution defective (hid) induction, resulting in caspase activation and cell death. We identify the CREB binding protein (CBP) transcriptional cofactor as essential for salivary gland cell death. We show that CBP acts 1 d before the onset of metamorphosis in apparent response to a mid-third instar ecdysone pulse, when CBP is necessary and sufficient for down-regulation of the Drosophila inhibitor of apoptosis 1 (DIAP1). It is only after DIAP1 levels are reduced that salivary glands become competent to die through rpr/hid-mediated cell death. Before this time, high levels of DIAP1 block salivary gland cell death, even in the presence of ectopic rpr expression. This study shows that naturally occurring changes in inhibitor of apoptosis levels can be critical for regulating cell death during development. It also provides a molecular mechanism for the acquisition of competence in steroid signaling pathways.